Human follicle stimulating hormone (hFSH) and thyroxine (T4) in survival maintenance and in vitro growth promotion of caprine preantral follicles - Costa, Sanely Lourenço da; Costa, Eduardo Paulino da; Pereira, Emílio César Martins [UNESP]; Gonçalves, Wagner Gonzaga; Silva, Talita Fernandes da; Queiroz, Vanessa Lopes Dias (Universidade Federal de Goiás, 2015)
The aim of this study was to investigate the interaction of human FSH (10ng/ml) with T4 (20ng/mL) on survival, activation and growth of preantral follicles cultured in vitro for 28 days. Fragments of non-cultured and cultured ovarian tissue were processed for classic histology and transmission electron microscopy. The results showed a reduction in the survival rate in all the media tested (one to 28 days) when compared to the fresh control. However the treatment with T4/hFSH for seven days of culture maintained the rate similar to the control. The media tested by one and 28 days reduced the percentage of primordial follicles in all periods of culture. However, T4/hFSH on day one of culture remained similar to the fresh control. None of the media were able to keep the percentage of the developing follicles. It was observed that the follicular diameter in the medium with T4/hFSH remained similar to the fresh control. The ultrastructural analysis confirmed the integrity of follicles cultured for seven days in a medium supplemented with T4/hFSH. In conclusion, the medium with T4/hFSH is able to maintain the survival, promote the activation, and the ultrastructural integrity of caprine preantral follicles for until seven days.

O objetivo deste estudo foi investigar a interação do FSH humano (10 ng/mL) com T4 (20 ng/mL) na sobrevivência, ativação e crescimento de folículos pré-antrais cultivados in vitro, por um período de longa duração (28 dias). Fragmentos de tecido ovariano não cultivado e cultivados foram processados para histologia clássica e microscopia eletrônica de transmissão. Os resultados mostraram uma redução na taxa de sobrevivência em todos os meios testados (um a 28 dias) quando comparado ao controle fresco. Entretanto, o tratamento com T4/hFSH por sete dias de cultivo resultou em taxa semelhante ao controle. Os meios testados por 28 dias reduziram o percentual de folículos primordiais em todos os períodos de cultivo. Contudo, T4/hFSH no dia um de cultivo manteve-se semelhante ao controle fresco. Nenhum dos meios foi capaz de manter o percentual dos folículos em desenvolvimento. Observou-se que o diâmetro folicular cultivado no meio com T4/hFSH manteve-se semelhante ao controle fresco. As análises ultraestruturais confirmaram a integridade de folículos cultivados por sete dias em meio suplementado com T4/hFSH.  Em conclusão, o meio com T4/hFSH é capaz de manter a sobrevivência, promover a ativação e a integridade ultraestrutural de folículos pré-antrais caprinos, por até sete dias.
Hormônio folículo estimulante humano (HFSH) e tiroxina (T4) na manutenção da sobrevivência e promoção do crescimento in vitro de folículos pré-antrais caprinos
Keywords: Activation; Caprine; hFSH; Preantral follicles; T4; Ativação; Caprino; Folículos pré-antrais; hFSH; T4